PENGARUH MOTIVASI KERJA, ETIKA KERJA ISLAMI DAN EVALUASI KINERJA TERHADAP KINERJA PEGAWAI DENGAN REMUNERASI SEBAGAI VARIABEL MODERASI DI STIS HIDAYATULLAH BALIKPAPAN - Nasikin, Nasikin; D, H.M Abzar; Mursyid, Mursyid (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The purpose of this study was to determine the effect of work motivation, Islamic work ethics, and performance evaluation on employee performance and to determine whether remuneration can moderate the relationship between work motivation, Islamic work ethics, and performance evaluation on employee performance. The method used is a survey with a structured questionnaire and data analysis using regression analysis techniques. The results of the study provide evidence that 1) work motivation has a positive and significant effect on employee performance at Hidayatullah Balikpapan College of Islamic Sciences (STIS). 2) that the Islamic work ethic has a positive and significant effect on employee performance at Hidayatullah Balikpapan College of Islamic Sciences (STIS). 3) that Performance Evaluation has a positive and significant effect on the performance of employees of the Hidayatullah Islamic College (STIS) Balikpapan. 4) that remuneration has a positive and significant effect on the performance of Hidayatullah Balikpapan College of Islamic Sciences (STIS) employees. 5) that work motivation, Islamic work ethics and Performance Evaluation have a positive and simultaneous effect on employee performance after being moderated by the existing remuneration at Hidayatullah Balikpapan College of Islamic Sciences (STIS) and this is proven by empirical evidence.